Bioindikator Makrozoobenthos dalam Penentuan Kualitas Perairan di Tukad Mati Badung, Bali - Widhiandari, Putu Frissa Anasthasya; Watiniasih, Ni Luh; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
Abstract Tukad Mati ( Mati River ) , is a river located in Badung regency. The amount of garbage that enters the river causes sedimentation in the estuary. The water in Tukad Mati becomes dirty and smells bad . There fore water . The degradation of water quality the living organisms . A number of   o rganisms can be functioning  as bio-indicators of water quality, such as macrozoobenthos. This study aims to determine Tukad Mati's status based on equitability index, diversity index, and dominance index of macrozoobenthos, and to determine water quality using biological indicators of macrozoobenthos with the Family Biotic Index (FBI) . Th e study was conducted i n November 2019. Samples were collected  from 3 stations and sampl es collections ware  repeated 4 times during the study. The highest abundance of macrozoobenthos at station I was Notopala sublineata species 6 ind/m 2 . station II was Semisulcospira libertina  5.16 ind/m 2 .  A nd station III was Lmynaea acuminata species at 5.56 ind/m 2 . The diversity index of station I was 2.68, station II was 2.49, and station III was 2.59. Dominance index at the three stations was 2. Similarity  index of station I was 0.99, station II was 0.92, and station III was 0.95. The FBI  value of station I was 6.32; station II was 6.22; station II was 6.23. Disolved oxygen (DO) range s from 6.67 to 7.72 mg/L; BOD 5 ranges from 9.21 -10.28 mg/L; pH ranges from 5.6 - 5.8; T he temperature during the stuy was on average of  30.1°C; the turbidity was  ranged form  8.16 - 9.84 NTU . The he  substrate of station I was rocky, sandy and muddy; station II was sandy; and station III was muddy sand y .   Keywords: Abundance; Biomonitoring, Makrozoobenthos; Water quality, Mati river